Construction of a Novel In Vitro Atherosclerotic Model from Geometry‐Tunable Artery Equivalents Engineered via In‐Bath Coaxial Cell Printing - Gao, Ge; Park, Wonbin; Kim, Byoung Soo; Ahn, Minjun; Chae, Suhun; Cho, Won‐Woo; Kim, Jisoo; Lee, Jae Yeon; Jang, Jinah; Cho, Dong‐Woo (Advanced functional materials, 2021)
As the main precursor of cardiovascular diseases, atherosclerosis is a complex inflammatory disorder that preferentially occurs in stenotic, curved, and branched arterial regions. Although various in vitro models are established to understand its pathology, reconstructing the native atherosclerotic environment that involves both co‐cultured cells and local turbulent flow singling remains challenging. This study develops an arterial construct via in‐bath coaxial cell printing that not only facilitates the direct fabrication of three‐layered conduits with tunable geometry and dimensions but also maintains structural stability. Functional vascular tissues, which respond to various stimulations that induce endothelial dysfunction, are rapidly generated in the constructed models. The presence of multiple vascular tissues under stenotic and tortuous turbulent flows allows the recapitulation of hallmark events in early atherosclerosis under physiological conditions. Furthermore, the fabricated models are utilized to investigate the individual and synergistic functions of cell co‐culture and local turbulent flows in regulating atherosclerotic initiation, as well as the dose‐dependent therapeutic effect of atorvastatin. These outcomes suggest that the constructed atherosclerotic model via a novel fabrication strategy is a promising platform to elucidate the pathophysiology of atherosclerosis and seek effective drugs and therapies. An advanced in vitro atherosclerosis model that enables the co‐culture of multiple vascular cells under local turbulent flows is developed from geometry‐tunable arterial constructs engineered by a novel in‐bath coaxial cell printing strategy. This platform recapitulates the hallmark events in early atherosclerosis and shows great potential for understanding the atherosclerotic pathophysiology and evaluating drug efficacy.